Beyond Sharia Compliance: How Islamic Economics and Trust Shape Purchase Intention in the Era of Hijrah Lifestyle - Ishma Ulfasari; Umu Khouroh (Jurnal Manajemen dan Kewirausahaan, 2025)
This study examines how Islamic economics influences consumers’ purchase intention toward sharia-compliant housing, emphasizing the mediating role of trust and the contextual influence of the hijrah lifestyle. Using data from 137 respondents and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that Islamic economics significantly strengthens both trust and purchase intention. Trust also plays a crucial mediating role, demonstrating that consumers’ confidence in developers’ sharia compliance, transparency, and ethical integrity is essential in converting religious–economic values into behavioral intentions. The hijrah lifestyle—reflecting religious identity, spiritual motivation, and community influence—shows a strong direct effect on purchase intention, although it does not moderate the relationships between Islamic economics and trust or purchase intention. Integrating the Theory of Planned Behavior (TPB), and Islamic Sustainability Theory, this study highlights that consumer intention to purchase sharia housing is shaped by value-driven attitudes, perceived behavioral control through trust, and spiritual identity. The results underscore the importance of ethical transparency, riba-free financial systems, and religious lifestyle alignment in strengthening the future growth of the sharia housing market.